Suicide attempt using zinc phosphide rodenticide: A case report and literature review. Issue 10 (6th October 2021) - Nekoukar, Zahra; Moghimi, Minoo; Rasouli, Kimia; Hoseini, Aref; Zakariaei, Zakaria; Tabaripour, Rabeeh; Fakhar, Mahdi; Banimostafavi, Elham Sadat
Abstract: The patients with a history of intentional or unintentional consumption of rodenticide compounds, especially ZnP, it is necessary to assess ABG and abdominal radiography. Abstract : In the patients with a history of intentional or unintentional consumption of rodenticide compounds, especially ZnP, it is necessary to assess ABG and abdominal radiography.